2016
DOI: 10.1002/aqc.2656
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal movements of immature Kemp's ridley sea turtles (Lepidochelys kempii) in the northern gulf of Mexico

Abstract: ABSTRACT1. Seasonal movements and core habitat areas of immature Kemp's ridley sea turtles (Lepidochelys kempii) in the northern Gulf of Mexico were tracked via satellite telemetry. Tagged turtles were incidentally captured by recreational fishermen and rehabilitated at the Institute for Marine Mammal Studies in Gulfport, Mississippi.2. The average size of the core habitat areas (50% KDE (kernel density estimation)) was 1660.2 km 2 ± 3438.2 SD. Turtles displayed strong intra-and inter-annual site fidelity to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…Therefore, in order for stranding to occur before carcasses dissociated due to decomposition, drift times and distances would have needed to be low (∼2-5 days, 15-30 km; Nero et al, 2013;Santos et al, 2018). Second, Kemp's ridleys display relatively high intra-and inter-annual site fidelity to nearshore, shallow (<50 m depth) foraging areas (generally <1,000 km 2 ) that are well constrained spatially within our defined geographic regions (Renaud and Williams, 2005;Schmid and Witzell, 2006;Shaver and Rubio, 2008;Seney and Landry, 2011;Coleman et al, 2017). Therefore, turtles that stranded within each geographic area are likely to have been foraging within their stranding location-assigned geographic area prior to death.…”
Section: Sea Turtle Stable Isotope Ratiosmentioning
confidence: 99%
“…Therefore, in order for stranding to occur before carcasses dissociated due to decomposition, drift times and distances would have needed to be low (∼2-5 days, 15-30 km; Nero et al, 2013;Santos et al, 2018). Second, Kemp's ridleys display relatively high intra-and inter-annual site fidelity to nearshore, shallow (<50 m depth) foraging areas (generally <1,000 km 2 ) that are well constrained spatially within our defined geographic regions (Renaud and Williams, 2005;Schmid and Witzell, 2006;Shaver and Rubio, 2008;Seney and Landry, 2011;Coleman et al, 2017). Therefore, turtles that stranded within each geographic area are likely to have been foraging within their stranding location-assigned geographic area prior to death.…”
Section: Sea Turtle Stable Isotope Ratiosmentioning
confidence: 99%
“…Previous studies recognized that sufficient habitat and forage would be required to accommodate this influx of juveniles [54] and indicated that carrying capacity for the population might be reached at smaller sizes than in the past and that an abrupt “crash” might occur [10, 11]. Both juvenile and adult Kemp’s ridleys exhibit site fidelity to GOM foraging areas [5460], with juveniles preferring shallower-water habitat [55, 57, 61, 62]. Furthermore, studies have reported that Kemp’s ridleys may specialize in their diet preferences, focusing on swimming crabs (in particular the blue crab, Callinectes sapidus ), with additional consumption of various walking crab species [58, 63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…• Turtles Satellite telemetry has been used to track the movement of turtles and changes. Coleman et al, 2017 [233] used a UUV attached to the back of sea turtles (called Platform Terminal Transmitter PPT) that is tracked with earth-orbiting satellite to follow the movement of turtles. The collected data showed changes that happened in the Mississippi-Gulf region.…”
Section: • Sea Birds and Marine Mammalsmentioning
confidence: 99%